Dobal sistema - López, Fernando; Camus, Guillermo; Domínguez, Guillermo (Auca: Arquitectura Urbanismo Construcción Arte, 2020)
Escuelas tipi 15-b (15 salas) Población Barrancas I m2 construídos 1671, Valor/m2 E°265,50